Understanding the Use of Acupuncture for Insomnia Among Cancer Survivors: A Qualitative Study - Eriksen, Whitney T. (J Altern Complement Med, 2018)
Objective: To understand cancer survivors' perceptions regarding the use of acupuncture for the treatment of cancer-related insomnia. Design: Semistructured interviews with cancer survivors participating in a randomized controlled trial comparing the effectiveness of Cognitive Behavioral Therapy for Insomnia (CBT-I) and acupuncture for the treatment of insomnia. Interviews were conducted before randomization into either treatment option, and structured to elicit participants' experiences with insomnia as well as their beliefs and understanding surrounding acupuncture for the treatment of insomnia. An integrated approach was used for data analysis. Subjects: Sixty-three cancer survivors with DSM-V diagnosed insomnia. Results: Participants shared a broad lack of understanding regarding acupuncture for the treatment of insomnia. Specifically, individuals in this study expressed confusion surrounding what symptoms or medical conditions acupuncture could be used to treat, how acupuncture works, and how long the effects of acupuncture last. Conclusions: This study identified three specific gaps in knowledge, including treatment target, mechanism, and durability, surrounding the use of acupuncture for insomnia in cancer survivors. Addressing these gaps by providing appropriate and timely education surrounding the use of acupuncture to treat insomnia is essential to increase the evidence-informed utilization of acupuncture and to better meet patients' needs among cancer survivors.